Academics boarding. - Guillén Araoz, Félix (2015)
In summary we can conclude: 1. In general, according to the latest medical education seminars, the current Internship meet halfway with the objectives set by the recommendations of national and international seminars. 2. Taking into account the needs of the community and the country's resources, it is recommended that the committees to review the curricula in the various programs of the country Medical Sciences, contemplate delete, or imprint substantial changes, because as has been done provides only a limited view of situations in which the physician future will face with the exercise of their profession. 3. Supervision of the work of Internal in teaching hospitals is little objection. Whereas in other types of hospitals leaves much to be desired because they are not meeting the minimum requirements of the Intersectoral Commission; precisely because it does not have adequate and operative mechanisms for evaluation and monitoring. As a contribution to the requirements to have full compliance is expected to ascribe such hospitals or affiliate with the Programs of Medical Sciences, their respective influence. This among other things, improve the scientific level of non-university hospitals. 4. participation in community Internal Services is accepted as a necessity that should be encouraged, given the multiple possibilities. In relation to the areas in which it can be carried out this share, the best are those that by their geographical location, allowing adequate supervision. 5. It clearly states that the boarding, being mandatory, should not be exploited to solve the provision of welfare services, and 6. That the internal is a student of the final year of medical studies, and, therefore, It can not be paid in any medical institution. This however, is not an impediment to receive economic aid (not by way of salary but scholarship or pecuniary assistance) etc., of their own program or the respective Medical Sciences Hospital. To prevent the economic value becomes an incentive to divert the student's academic interest, the unification of that allowance is recommended at national level.